Rutting Prediction of Hot Mix Asphalt Mixtures Modified by Nano Silica and Subjected to Aging Process - Zainab Kadhim Taher; Mohammed Q. Ismael (Civil Engineering Journal, 2023)
High-volume traffic with ultra-heavy axle loads combined with extremely hot weather conditions increases the propagation of rutting in flexible pavement road networks. Several studies suggested using nanomaterials in asphalt modification to delay the deterioration of asphalt pavement. The current work aims to improve the resistance of hot mix asphalt (HMA) to rutting by incorporating Nano Silica (NS) in specific concentrations. NS was blended into asphalt mixtures in concentrations of 2, 4, and 6% by weight of the binder. The behavior of asphalt mixtures subjected to aging was investigated at different stages (short-term and long-term aging). The performance characteristics of the asphalt mixtures were evaluated using the Marshall stability, flow, and wheel tracking tests. Field Emission Scanning Electron Microscopy (FESEM) was utilized to understand the microstructure changes of modified asphalt and estimate the dispersion of NS within the asphalt. The results revealed that using NS–asphalt mixtures as a surface layer in paving construction improved pavement performance by increasing stability, volumetric characteristics, and rutting resistance before and after aging. The FESEM images showed adequate dispersion of NS particles in the mixture. Results indicated that adding 4% of NS to asphalt mixtures effectively enhanced the pavement’s performance and rutting resistance. Doi: 10.28991/CEJ-SP2023-09-01 Full Text: PDF